Urban government for metropolitan Lagos - Williams, Babatunde Abraham; Walsh, Annmarie Hauck (New York: Praeger, 1968)
The discussions/descriptions in the book have been split into six chapters. Chapter 1 discusses the dimensions of the region. Chapter 2 examines governmental institutions for Lagos. Chapter 3 deals with intergovernmental relationships. Chapter 4 describes the planning for Lagos. Chapter 5 deals with selected urban services in Lagos, and Chapter 6 reviews comparative trends and problems in urban administration.
Praeger special studies in international politics and public affairs.
Includes bibliographical references.
ne 03/07/2018
Loans
Keywords: Urban administration; Lagos